An open multi-user platform in support of urban development: the DATA WebGIS. - Pristeri, Guglielmo; Pappalardo, Salvatore; Codato, Daniele; Gianoli, Federico; De Marchi, Massimo (My University, 2018)
One of the key features of our times is the availability of a huge amount of digital data regarding any branch of knowledge or human activity, combined with the widespread diffusion of devices connected to the web. Besides, the potential of data mining and processing offered by contemporary ICT is constantly growing. Turning these capabilities into opportunities and advantages is a challenge involving a lot of research areas. In the field of urban and territorial studies, free and open access to spatial data is by now a common policy for national and international institutions: an example is the INSPIRE Directive by European Union, which sets a framework for Spatial Data Infrastructures by its member states. As a consequence, georeferenced data and thematic maps concerning cities and their surrounding territory are released for public consultation by administrations and monitoring agencies. Nevertheless, this proliferation of data is not always accompanied by an improvement of spatial planning quality: in western cities, economic crisis and functional obsolescence can take to decommission or underuse of buildings and compounds, both public and private; at the same time, a circular and environmentally-friendly vision of urban development is still struggling to gain acceptance in practices. In order to reactivate complex urban or peri-urban areas, traditional planning shall therefore lean on different research fields in a multidisciplinary vision. Proposed scenarios should be sustainable, and take advantage of new ways of thinking and acting bred by the advancement of digital geo-information technologies. DATA Developing Abandoned Transurban Areas is a research project financed by European Social Funds, involving Departments of Civil, Environmental and Architectural Engineering and Industrial Engineering of the University of Padova and fitting in the framework described above. It aims to generate pilot transformation scenarios for abandoned areas awaiting regeneration. The chosen sample region is a part of the western periphery of Padova, in the North East of Italy, marked by a mix of rural and built surfaces, infrastructures and partially abandoned building complexes. One of DATA topics is to collect and process multi-scale data related to the region of interest, for the purpose of releasing them on an open source webGIS platform, thus spreading knowledge outside the academic field and creating interactions with involved urban actors. Collected data include base city maps, social and environmental information, historical evolution of the studied area, urban development plans. Their processing is developed through an open source workflow, from QGIS software to a GeoNode web platform, and their combination produces integrated information layers and in-depth analysis about the nodes of possible urban transformations. This paper introduces data and GIS-based analysis feeding the platform, together with its fruition levels: the webGIS in fact addresses to different users' categories, including the research group itself, public and private stakeholders that may be interested in starting new urban projects, active citizens and associations willing to participate in the processes of development. The final goal is to keep the platform working beyond the end of the research project, as a base framework for the futures of the area.
Keywords: Geodaten; Geoinformationssystem; Stadtplanung; Raumplanung